2012
DOI: 10.1155/2012/630425
|View full text |Cite
|
Sign up to set email alerts
|

Fe(III)-Citrate-Complex-Induced Photooxidation of 3-Methylphenol in Aqueous Solution

Abstract: The photodegradation process of m-cresol (3-methylphenol), induced by Fe(III)-Cit complex, was investigated upon irradiation at 365 nm in natural water. The composition and photochemical properties of Fe(III)-Cit complex were studied by UV-Visible absorption spectrophotometer for optimizing the stoichiometry of the complex and photolysis under irradiation at 365 nm, respectively. A dark investigation of the system was performed before studying the photochemical behavior. The photooxidation efficiencies of m-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Visible light photo response is impossible with zeolites or alumino silicates without impurities, as they do not absorb visible light with the inorganic semiconductor . NH 2 substitution in either of 1,4‐benzenedicarboxylic acid or aromatic Polycarboxylate helps to insert a fresh band in the visible region having the λ max at 400 nm . This is to be noted that same technique can be followed for the synthesis of both the un‐substituted or amine substituted MOF which are iso‐structural to each other.…”
Section: Journey Of Mof As Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible light photo response is impossible with zeolites or alumino silicates without impurities, as they do not absorb visible light with the inorganic semiconductor . NH 2 substitution in either of 1,4‐benzenedicarboxylic acid or aromatic Polycarboxylate helps to insert a fresh band in the visible region having the λ max at 400 nm . This is to be noted that same technique can be followed for the synthesis of both the un‐substituted or amine substituted MOF which are iso‐structural to each other.…”
Section: Journey Of Mof As Photocatalystmentioning
confidence: 99%
“…[75] NH 2 substitution in either of 1,4-benzenedicarboxylic acid or aromatic Polycarboxylate helps to insert a fresh band in the visible region having the l max at 400 nm. [76] This is to be noted that same technique can be followed for the synthesis of both the un-substituted or amine substituted MOF which are iso-structural to each other. Visible light photo response is possible by choosing either porphyrin or polypyridyl as linker.…”
Section: Journey Of Mof As Photocatalystmentioning
confidence: 99%
“…et al 1993) except in the 2.2-2.7 eV photon energy range that matches the PBTh band gap. The contribution of the dopant to the charge transfer process was explained on a basis that the reaction between incident light and charges of the material will take place as a result of absorption of photon energy by the assembly (Seraghni N. et al, 2012). The presence of CdO 2 /CdO enhanced the process that leads to polarizing the charges of the material.…”
Section: Optical Parametersmentioning
confidence: 99%
“…During its lifetime, this anion radical acted as a temporary molecular paramagnet (Seraghni N. et al 2012) that interfered with the applied a magnetic field and generated the recorded photocurrent outcome as shown in Figures 7-9. …”
mentioning
confidence: 99%
“…[35][36][37] Also, it was observed that Fe 3+ ions gave a stable complex with chlorphenamine, having a similar structure to histamine, at pH 6.0 (log b: 3.6 at ratio of 1 : 1). For this purpose, preliminary experiments were carried out with metal ions including Fe(III), Cu(II), and Sn(IV) at isomolar concentrations.…”
Section: Optimization Of the Variables Affecting Complex Formation Anmentioning
confidence: 99%